PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN KEPUASAN KERJA SEBAGAI MEDIASI - Yasno, 11.52.02.0032 (Students Journal of Economic and Management, 2013)
This study aims to identify and examine the influence of discipline, work ethic on the performance of job satisfaction with mediation that takes teachers of public Junior High School in Kudus Regency as the object. Sampling was done by purposive sampling technique. From the results of purposive sampling, the samples used in this study are 204 people. Data testing techniques used in the study are test validity with factor analysis, reliability tests with Cronbach alpha formula, the multiple regression analysis, and tests of significance, the coefficient of determination to prove the truth of the hypothesis and test mediation. The results shows that the variable of headmaster leadership, work motivation, and job satisfaction have a positive and significant influence on performance. Keywords: Leadership, Motivation, Satisfaction and Performance